Editorial (2021)
The Universidad Santo Tomas, Seccional Tunja, presents the journal Principia Iuris No. 37, which develops topics of vital importance for legal progress, conceived from the social projection, and with axiological and epistemological bases that contribute to the solution of the different problems of disciplinary and interdisciplinary research. The research in this edition represents the deployment of topics that cover important philosophical and legal issues, both in a national and international context. The articles are devoted to biolaw, legal psychology, human _ rights, constitutionalism and philosophy of criminal law, among others. Thus, the reader will find a very provocative constellation of philosophical-legal issues in this issue. Our journal is indexed in EBSCO, Latindex, Publindex, Google Scholar, OpenAIRE and Open Archives. As always, the permanent and tireless effort of the jurists and participants of this edition is highlighted by us and, with its greatness, by the whole science of law.